Pengaruh Board Game terhadap Pemahaman Konsep IPAS pada Siswa Kelas V Sekolah Dasar - Nur Afna Juanda; Atep Sujana; Enjang Yusup Ali (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The problem in this research is that students have not been able to explain the human respiratory process studied with their own understanding, students feel learning is not fun because of the lack of good supporting media. So, the aim of this research is to obtain an overview of the influence of using the Board Game "Snakes and Ladders" on students' conceptual understanding of the human respiratory system material. The research method used was pre-experiment with a One Group Pretest-Posttest research design. The research results obtained were then analyzed using the N-gain test and Paired Sample-T-Test. The results of the research show an increase in the average posttest score after implementing the "Snakes and Ladders" media Board Game support by 31%, with a pretest average of 53 and a posttest score of 84. Paired Sample t-Test analysis also shows a significance of 0.000 < 0.05 so that Ho is rejected and Ha is accepted. The level of effectiveness is verified through the N-Gain test at 68% which places it in the quite effective category. Based on this explanation, it can be concluded that through the use of the Board Game "Snakes and Ladders" learning media, this research recorded a positive impact on class V students' conceptual understanding of the human respiratory system material.